2013
DOI: 10.1210/jc.2013-2649
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Pituitary-Adrenal Axis Recovery Following Prolonged Prednisolone Therapy in Infants

Abstract: HPA recovery occurred within 6 to 12 weeks, shorter than empirical recommendations, to give stress cover for 6 to 12 months. Reduced duration of stress-cover precautions may reduce parental anxiety and side effects from unnecessary glucocorticoid use. Healthy control infants established circadian variation in salivary cortisol between 2 and 6 months of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…However, if the duration of therapy is 3 weeks or longer, it is recommended that the glucocorticoid dose be tapered gradually to avoid precipitating symptoms of steroid dependence and/or AI 12. Protracted use of supraphysiological glucocorticoid doses may result in severe adrenal gland atrophy and prolonged AI lasting up to 34 weeks requiring glucocorticoid tapering to be extended over many months 13 14…”
Section: Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the duration of therapy is 3 weeks or longer, it is recommended that the glucocorticoid dose be tapered gradually to avoid precipitating symptoms of steroid dependence and/or AI 12. Protracted use of supraphysiological glucocorticoid doses may result in severe adrenal gland atrophy and prolonged AI lasting up to 34 weeks requiring glucocorticoid tapering to be extended over many months 13 14…”
Section: Etiologymentioning
confidence: 99%
“…Therefore, it is important to recognize chronic ICS therapy as a risk factor for AI. A study of infants with hemangiomas treated with high-dose glucocorticoid therapy for 12–26 weeks demonstrated the return of normal circadian response in salivary cortisol levels within 6 weeks and normal response to administration of low-dose ACTH stimulation by 12 weeks after stopping treatment 14…”
Section: Etiologymentioning
confidence: 99%
“…Mendoza-Cruz et al (6) looked into duration of HPA axis suppression in infants treated with prednisolone. The infants received high dose of prednisolone for an average of 3-6 months, weaned over 4-6 weeks.…”
Section: Glucocorticoid Use In Hemangiomamentioning
confidence: 99%
“…Some studies have demonstrated longer HPA-axis suppression during treatment of childhood ALL and brain tumors [101][102][103][104][105][106]. Changes in HPA-axis activity were shown to lead to learning and memory difficulties in animals [98].…”
Section: Hpa-axis Functioning: Hormonal Changes and Stressmentioning
confidence: 99%